Hasanov, Kanan - (:unkn) unknown (My University, 2026)
Kanan Kamran Hasanov graduated with distinction from the Azerbaijan University of Architecture and Construction (AzUAC) in 2013 with a Bachelor’s degree in Organization and Management of Industry. In 2015, he completed a Master’s degree with distinction in Information Technology Management at the University of Nottingham, United Kingdom, supported by the State Program on Education of Azerbaijani Youth Abroad. Since 2017, he has been working as a Senior Lecturer at the Department of Economic Theory and Marketing at AzUAC, teaching courses in Economic Regulation, Azerbaijan Economy, Marketing, and related subjects. Since October 2025, he has also served as Head of the Sustainable Development Center at AzUAC. Since 2020, he has been pursuing doctoral studies in 5312.01 – Sectoral Economics, with research focusing on Human Capital Management in the Digital Economy. He has extensive professional experience in project management, marketing, research, and consulting. Since October 2025, he has served as Director of ERA Consulting LLC. His research interests include the digital economy, human capital and human resource management, smart cities, sustainable development, digital transformation, and contemporary management approaches. He has published in Scopus-indexed journals and presented research at national and international conferences.